PROFESSIONALISM IN ADULT EDUCATION: THE SUREST WAY FOR EFFECTIVE ADMINISTRATION OF ADULT EDUCATION IN NIGERIA - Muhammad, Alkali (Sokoto Educational Review, 2020)
The quality or output of any organisation or programme depends to a very large extent on the competence and efficiency of its human resources or personnel. All serious minded organisations spend a very high percentage of their capital in manpower development in order to bring out the quality of the goods or services that will stand them out for success. The need for adequate training and retraining of the human resource of any organisation becomes a matter of optimum survival and at such cannot be toyed with. It is therefore pertinent that the issues of qualified personnel’s and professionalism be given a second more serious attention if adult education must contribute to national development. Consequently in adult education being a very important component of education for the socio-economic development of any nation can only succeed if professionalism is given its rightful place. This paper therefore seeks to look into ways Adult education management can be effective in Nigeria through ensuring professionalism.